Is it time for developing countries to adopt neonatal pulse oximetry screening for critical congenital heart disease? - Zühlke, Liesl; Vaidyanathan, Balu (SA Heart Journal, 2017)
Critical congenital heart disease is often missed with resultant death or severe circulatory collapse and morbidity. Pulse oximetry screening has now been recommended for use in the United States of America and adopted in other developed world settings as part of the compulsory newborn screening programme. In this review we detail the rationale behind neonatal pulse oximetry screening, summarise the recent evidence and present data on method, cost-effectiveness and acceptance. However, differences in health systems in the developed world and developing countries are clearly refl ected in the discrepancies in management and outcome of congenital heart disease. We discuss the importance of embedding a neonatal screening programme within local situations and suggest a method, using the infant mortality rate and other neonatal indicators, to position neonatal pulse oximetry screening into existing newborn screening programmes.